ANALYSIS OF THE DEVELOPMENT OF PT'S FINANCIAL PERFORMANCE. BANK RAKYAT INDONESIA WHICH GOES PUBLIC ON THE INDONESIAN STOCK EXCHANGE - Laura Angelina; Haeril Haeril; Jumriah Basri (Journal Of Accounting And Finance, 2025)
In the 2020-2022 period the financial performance of PT. Bank Rakyat Indonesia experienced fluctuations which gave a bad signal to stakeholders. Therefore, this research aims to analyze the financial performance ratios of PT. Bank Rakyat Indonesia from 2020-2022 using liquidity, solvency and profitability ratios. This research uses quantitative descriptive methods. The data used is secondary data in the form of PT's financial reports. Bank Rakyat Indonesia is published on the Indonesian Stock Exchange using data collection methods, namely documentation techniques. The data analysis technique used is using ratio analysis techniques in the form of liquidity consisting of the Current Ratio and Quick Ratio, solvency consisting of the Debt to Assets Ratio and Debt to Equity Ratio, and profitability consisting of Return on Assets and Return on Equity. The research results show that liquidity ratios, both CR and QR, have decreased but the percentages meet established industry standards so they are in the "good" category. The solvency ratio, namely the DAR, fluctuates with a percentage that does not meet industry standards so it is categorized as "not good", while the DER also fluctuates but the percentage meets industry standards so it is categorized as "good". As for profitability ratios, ROA and ROE experienced successive increases in each period but did not meet industry standards so they were categorized as "poor".